Antimicrobial and bactericidal impacts of Bacillus amyloliquefaciens CECT 5940 on fecal shedding of pathogenic bacteria in dairy calves and adult dogs. (January 2018) - Vazquez-Mendoza, Paulina; Elghandour, Mona M.M.; Alaba, Peter Adeniyi; Sánchez-Aparicio, Pedro; Alonso-Fresán, María Uxúa; Barbabosa-Pliego, Alberto; Salem, Abdelfattah Z.M.
Abstract: Two experiments were carried out to evaluate the bactericidal impacts of Bacillus amyloliquefaciens CECT 5940 on the shedding of faecal pathogenic bacteria in dairy calves (Experiment 1) and in adults dogs (experiment 2). In the calves experiment, a completely randomized design was used to investigate the faecal bacteria profile of Holstein dairy calves fed with either pasteurized waste milk (PWM; n = 9) or a formulated non-medicated milk replacer (NMR; n = 9) for 60 d. The NMR containing sodium-butyrate and the active probiotic B. amyloliquefaciens CECT 5940. In the dogs experiment, addition of same probiotic (i.e., B. amyloliquefaciens CECT 5940) was carried out in two stages. The first stage started from day 7–37, and the second from day 44–71. The assessment of faecal score measured on day 22, 37, 42, 57, 71 and 77 to determine the texture of the stools. Calves received PWM consumed (P < 0.05) more starter feed between day 16 and day 45. The calves fed NMR had more moisture faeces and less cough reflux than the PWM-calves. Feeding NMR to calves increased faecal Klebsiella oxytoca and Proteus vulgaris counts in comparison to PWM-calves. The administration of B. amyloliquefaciens CECT 5940 to the dog diet has no significant effect on the hardness of the stool. Meanwhile, the bacillus count increases while the coliforms count decreases upon B. amyloliquefaciens CECT 5940 administration. This reveals that B. amyloliquefaciens CECT 5940 survived the gastrointestinal passage and rapidly colonized the dog intestine, which could positively affect the metabolism and composition of the intestinal microflora. These results show that B. amyloliquefaciens are a promising probiotic with an antimicrobial and bactericidal activities against the intestinal pathogenic bacteria for dairy calves and adult dogs. Highlights: B. amyloliquefaciens addition to animal diet has significant health benefits. K. oxytoca and P. vulgaris counts are observed in NMR-calves but not in PWM-calves. Lack of K. oxytoca and P. vulgaris in PWM-calves is because it contains antibiotics. Addition of B. amyloliquefaciens to dog diet did not affect the faecal score. B. amyloliquefaciens survived intestinal passage and colonized dog intestine. B. amyloliquefaciens has antimicrobial and bactericidal impacts on harmful bacteria.